A Mobile-Based Used Vehicle Buying System Implementation - Permana, Diky Oktiadi; Fachrie, Muhammad (International Journal Software Engineering and Computer Science (IJSECS), 2023)
Aspect-oriented software is characterized by enhanced reusability and maintainability compared to object-oriented software. In aspect-oriented software development, concerns scattered across objects are separated and modularized into aspects. This research is motivated by the buyer's mistrust in used vehicle transactions due to concerns over potential fraud. To address this, the study proposes designing an e-commerce application that facilitates interactions between prospective vehicle sellers and buyers, alleviating transactional apprehensions. The analysis and design phases of the software development cycle employ Use Cases to facilitate the identification and separation of concerns. Use Cases are chosen for their direct illustration of user-system interactions. The case study focuses on a mobile e-commerce application for used vehicle sellers and buyers. The research aims to analyze the impact of consumer motivation, perceived quality, and consumer attitudes on the decision to purchase used vehicles. The findings are expected to aid sellers in marketing their vehicles and assist buyers in making informed purchasing decisions